The Education and Blood Sugar Level Checks for Diabetes Mellitus Patients : Edukasi dan Cek KGD - Zulfahri Lubis; Sukma Yunita; Masdalifa Pasaribu; Herlia Sumardha Nasution; Fitriani (Jurnal Pengabdian Keperawatan Dan Kesehatan Holistik, 2026)
Abstract: Diabetes Mellitus (DM) has become a global health problem, particularly in developing countries due to the high rate of complications. Therefore, a healthy lifestyle must be adopted to avoid DM and its complications. The purpose of this community service is to provide an understanding of the importance of preventing and managing complications of DM through healthy lifestyle education. The community service method was carried out through health checks, such as blood sugar levels, blood pressure, and weight, and providing counseling to 15 elderly people in Sait Buttu' Village, Pematang Sidamanik District, Simalungun Regency. The education was implemented using lectures, discussions, and demonstrations. The analysis results showed that the level of knowledge of the Sait Buttu Village community, Sidamanik District, about DM is still low. Blood sugar examination results showed that the majority of DM sufferers have high blood sugar. Process evaluation demonstrated participant activeness from the beginning to the end of the activity. The conclusion of this community service is that counseling can increase knowledge about DM. It is recommended that education and blood sugar checks for DM sufferers be carried out early in their productive years as a preventative measure and to prevent complications.